Handbook of applied health economics in vaccines - Bishai, David; Brenzel, Logan; Padula, William (Handbooks in health economic evaluation series, 2022)
Fundamentals matter. Vaccines are some of the most complex molecules ever invented and, the social systems that deploy, monitor, and finance them are equally complex. Much of the peculiarities of vaccine economics arises from the peculiarities of vaccines. The most eccentric thing about vaccines is that many of them can benefit the person who gets the shot as well as the people around them. Furthermore, not everyone will obtain the same amount of benefit because of varying risk levels in the population. COVID-19 vaccines illustrate these points well. The massive public investments to subsidize supply and stimulate demand of COVID-19 vaccines were predicated on a sure forecast that without public investment the free market was doomed to fail. In many countries, even with the public sector investments, a COVID-19 vaccine at a price of $0 was not attractive to many who were at lower risk and did not appreciate the benefits their shot would offer their community"--